Genome wide expression analysis of circular RNAs in mammary epithelial cells of cattle revealed difference in milk synthesis - Ahmad, Syed Mudasir; Bhat, Basharat; Manzoor, Zainab; Dar, Mashooq Ahmad; Taban, Qamar; Ibeagha-Awemu, Eveline M.; Shabir, Nadeem; Hussain, Mohd Isfaqul; Shah, Riaz A.; Ganai, Nazir A. (PeerJ, 2022)
Milk is an excellent source of nutrients for humans. Therefore, in order to enhance the quality and production of milk in cattle, it is interesting to examine the underlying mechanisms. A number of new investigations and research have found that, circRNA; a specific class of non-coding RNAs, is linked with the development of mammary gland and lactation. In the present study, genome wide identification and expression of the circRNAs in mammary epithelial cells of two distinct cattle breeds viz Jersey and Kashmiri at peak lactation was conducted. We reported 1554 and 1286 circRNA in Jersey and Kashmiri cattle, respectively, with 21 circRNAs being differentially expressed in the two breeds. The developmental genes of the established differentially expressed circRNAs were found to be largely enriched in antioxidant activity, progesterone, estradiol, lipid, growth hormone, and drug response. Certain pathways like MAPK, IP3K and immune response pathways were found significantly enriched in KEGG analysis. These results add to our understanding of the controlling mechanisms connected with the lactation process, as well as the function of circRNAs in bovine milk synthesis. Additionally, the comparative analysis of differentially expressed circRNAs showed significant conservation across different species.
Keywords: CircRNA; Mammary gland; Bovine; RNA-Seq; Identification; Differential expression